E4 Transfer (E=P, As) to Ni Complexes. Issue 45 (1st June 2021) - Heinl, Veronika; Schmidt, Monika; Eckhardt, Maria; Eberl, Miriam; Seitz, Andreas E.; Balázs, Gábor; Seidl, Michael; Scheer, Manfred
Abstract: The use of [Cp′′2 Zr(η 1:1 ‐E4 )] (E=P (1 a ), As (1 b ), Cp′′=1, 3‐di‐ tert ‐butyl‐cyclopentadienyl) as phosphorus or arsenic source, respectively, gives access to novel stable polypnictogen transition metal complexes at ambient temperatures. The reaction of 1 a/1 b with [Cp R NiBr]2 (Cp R =Cp Bn (1, 2, 3, 4, 5‐pentabenzyl‐cyclopentadienyl), Cp′′′ (1, 2, 4‐tri‐ tert ‐butyl‐cyclopentadienyl)) was studied, to yield novel complexes depending on steric effects and stoichiometric ratios. Besides the transfer of the complete En unit, a degradation as well as aggregation can be observed. Thus, the prismane derivatives [(Cp′′′Ni)2 (μ, η 3:3 ‐E4 )] (2 a (E=P); 2 b (E=As)) or the arsenic containing cubane [(Cp′′′Ni)3 (μ3 ‐As)(As4 )] (5 ) are formed. Furthermore, the bromine bridged cubanes of the type [(Cp R Ni)3 Ni(μ‐Br)(μ3 ‐E)4 ]2 (Cp R =Cp′′′: 6 a (E=P), 6 b (E=As), Cp R =Cp Bn : 8 a (E=P), 8 b (E=As)) can be isolated. Here, a stepwise transfer of En units is possible, with a cyclo‐E4 2− ligand being introduced and unprecedented triple‐decker compounds of the type [(Cp R Ni)3 Ni(μ3 ‐E)4 2 (μ, η 4:4 ‐E′4 )] (Cp R =Cp Bn, Cp′′′; E/E′=P, As) are obtained. Abstract : Accessing the inaccessible : The use of the polypnictogen zirconium complexes [Cp′′2 Zr( η 1:1 ‐E4 )] (E=P, As) at ambient temperatures as phosphorus or arsenic sources to transfer E4 units to Cp R Ni fragments was examined. This avoids the difficulty of handling and toxicity of white phosphorus and yellow arsenic. The transfer reactions gave access to a variety of polypnictogen transition metal complexes, among them unprecedented triple‐decker‐like compounds composed of cage entities as end‐decks.